Dinamika Online Persona Akun Anonim Twitter Penggemar KPop - Kirana Wistiani Ayundari; Pulung Setiosuci Perbawani (Universitas Gadjah Mada, 2021)
This article addresses the psychological aspect of the need for comfort and freedom of self expression among KPop fans, which actualized through anonym account on twitter. KPop is one of the so-called interest whichhas some activities that always being compared to fanastim and still can't be accepted freely to general public. As part of the minorities, KPop fans are seeking for a place that could give them freedom for presenng their identities as fans who are actively participating in KPop fandom activities, and that place is none other than using pseudonym account on Twitter.A survey of 400 respondents who are using KPop anonym account on Twitter showed that privacy is the reason for 300 respondents to use anonymous accounts. The results of the mean test on the five dimensions of online persona variables are nickname (3.59), trust (3.78), online idenfication (3.44), grandiosity (3.09), and self-esteem (2.97). The results of the mean test on the group dynamics variable dimensions are connection (3.37), supportive interaction (3.07), affective (4.05), and cognitive (4.16). Seeking for a privacy and entertainment as a form of seperating themselves from face-to-face environment could give KPop fans to interact more about their KPop interests or even talking about their private lives through virtual environments, which is Twitter.Through interacons by using pseudonym, there are times when KPop fans are not just talking about theirKPop interests, but also showing their idenes and also their private lives as a phase when they're interacting with other KPop fans. Therefore, these could lead to an enchancement where solidarity are felt within KPop fandom in Twitter, and this could also give each KPop fans the feeling of being accepted and feeling lucky when they couldn't present themselves freely in a real life before and here they become more open and happy on this Twitter environment.